(untitled) (CIPEEX, 2025)
Introduction: In hernia repair, the benefits of the robotic system include high-quality 3D visualization of the abdominal cavity, increased motion, allowing for easier dissection of multiple adhesions, release of the rectus muscle, intraperitoneal mesh suturing, and complex abdominal wall reconstruction. Therefore, with the advancement of minimally invasive surgery, a comparative study between traditional surgery and robotic surgery in hernia repair is important to elucidate the true advantages, limitations, and future prospects within this field. Objective: To review and compare the use of robotic surgery and traditional surgery in hernia repair, highlighting their advances, clinical benefits, technical and economic limitations, as well as future prospects for surgical practice. Methodology: This is an integrative literature review based on seven articles. The health science descriptors used were: "Robotic Surgical Procedures," "General Surgery," "Surgical Procedures, Operative," "Hernia," "Hernia, Inguinal," "Hernia, Ventral," and "Hernia, Abdominal," with the Boolean operators AND and OR applied. Free articles published in the last five years, available in the PubMed database, consistent with the purpose of analyzing the use of robotic surgery and traditional surgery in hernia repair, available in English, Portuguese, or Spanish, and classified as randomized clinical trials, systematic reviews, or meta-analyses, were included. Texts inconsistent with the topic were excluded. Results and Discussion: Robotic hernia repair surgery has demonstrated shorter hospital stays, longer operative times, and its minimally invasive nature results in less tissue damage and a lower inflammatory response than open procedures. This has resulted in improved wound healing, with fewer adhesions and scar formation, further reducing the risk of hernia recurrence. Furthermore, the greater stability and precision of robotic surgical platforms minimize adverse events caused by tremors or hand fatigue. The articulated instruments of the robotic system overcome the angular constraints associated with traditional laparoscopic surgery, potentially aiding in more successful closure of hernia defects. Therefore, in economic terms, there was an increase in financial costs due to the greater use of operating room resources and the initial costs of robotic consoles and instruments, as well as the investment in training for all healthcare professionals involved in the surgical team. Conclusion: Robotic surgery is an evolution of the minimally invasive approach that maintains clinical outcomes at least equivalent to traditional techniques in many scenarios and can outperform the open approach in wound complications and length of hospital stay in complex repairs. However, longer operative time and high costs remain the main limitations. Patient selection, team experience, and local infrastructure are crucial to capturing benefits. Robust comparative studies, stratified by hernia type and technique, and standardized economic analyses are priorities to consolidate indications.